Pengaruh Model Problem Based Learning Terhadap Kemampuan Kognitif dan Keterampilan Berpikir Kritis - Samsudin, Samsudin; Sekarwinahyu, Mestika (Universitas Pakuan, 2023)
THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL ON COGNITIVE ABILITIES AND CRITICAL THINKING SKILLSThis study aims to determine whether the Cooperative learning model of the Think Pair Share type can increase the activity and learning achievement of students in the mathematics subject of calculating the volume of triangular prisms and circular tubes in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018 Academic Year/ 2019. To define the process of increasing activity and learning achievement of students in Mathematics about calculating the volume of triangular prisms and circular tubes after applying the Type Think Pair Share Cooperative learning model in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018/2019 Academic Year. To measure the magnitude of the increase in activity and learning achievement of students in mathematics lessons about calculating the volume of triangular prisms and circular tubes after using the Cooperative learning model type Think Pair Share in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City Semester 1 of the 2018/2019 Academic Year. The results of this study indicate that using the Cooperative learning model of the Think Pair Share type can be a fun variation of learning for students so it is proven to increase the activity and learning achievement of students in Class VI B SD Negeri Kertamaya, South Bogor District, Bogor City. Before using the Cooperative learning model type Think Pair Share activities and learning achievement of students only reached an average value of 64.50 then there was an increase after using the Cooperative learning model type Think Pair Share to 73.25 in cycle 1 and 81.37 in cycle 2 From the description above, the researcher concludes that the use of the Cooperative learning model type Think Pair Share is fun so that there is an increase in the activity and learning achievement of students. Therefore the researchers suggest that the use of the Cooperative learning model type Think Pair Share is disseminated and used as an alternative in learning mathematics in schools within the Bogor City Education Office.